Effect of a rubber plantation on termite diversity in Melawi, West Kalimantan, Indonesia - Hidayat, Mohamad Rusdi; Endris, Wahyu Maulana; Dwiyanti, Yulia (Agriculture and Natural Resources, 2018)
One of the negative effects of rubber plantation expansion is the loss of biodiversity in the area. One of the widely used rubber plantation systems is rubber forest agroforestry, which is known to have little effect on biodiversity. This study compared termite species in rubber forest with those in the primary forest within Bukit Baka Bukit Raya National Park in Melawi, Indonesia. Two rubber forest sites (newly opened) and unproductive/old rubber forest, were chosen to estimate the long term effects of rubber forest on termite biodiversity. A standardized transect method was used for termite collection. In total, 35 termite species belonging to eight sub families were collected. Termite species richness in the old rubber forest decreased up to 62.5% compared to that in primary forest sites. In the newly opened rubber forest site, termite species richness was only slightly less than that of the primary forest sites. Termite species richness results corresponded with their functional groups, with no soil feeders found in the old rubber forest. Furthermore, the calculation of several diversity indices also confirmed the results. The results indicated that the expansion of rubber forest in the area appears to have adversely affected termite diversity more than expected.